Analisis Kualitas Pelayanan Paspor Di Kantor Imigrasi Kelas 1 Non TPI Pemalang, Jawa Tengah - Moh. Elang Virgiawan; Yuniar Istiyani (Lembaga Pengembangan Kinerja Dosen, 2024)
Passport services at the Class 1 Non TPI Immigration Office in Pemalang, Central Java are oriented towards public satisfaction by not abandoning the principles of excellent service, which include: simplicity, clarity, certainty of time, accuracy, security, responsibility, completeness of facilities and infrastructure, convenience access, discipline, politeness and friendliness, as well as comfort. As well as having standards, namely: legal basis, requirements, systems, mechanisms, procedures, settlement period, costs/tariffs, service products, facilities and infrastructure, implementing competence, internal supervision, complaint handling , suggestions, input, number of implementers, service guarantees that provide certainty of time, security and safety guarantees, as well as evaluation of implementer performance.The purpose of this research is to evaluate the level of service provided by the Class 1 Non TPI Immigration Office, Pemalang, Central Java in making passports. This research uses observation, documentation and interviews as data collection methods, with a qualitative descriptive approach.The results show that the Central Java Non-TPI Class 1 Immigration Office in Pemalang usually offers competent passport issuance services. This conclusion is based on an assessment of service quality elements such as dependability, responsiveness, assurance, empathy, and concrete evidence. However, the report also identified a number of challenges, such as staff shortages and a lack of facilities and equipment.The Class 1 Non TPI Immigration Office in Pemalang, Central Java must take a number of steps to improve the quality of its services. These include increasing the number of employees, training to improve human resource capabilities, improving and completing facilities and infrastructure, as well as increasing community collaboration and communication. The office's goal in implementing these changes is to provide services that are faster, easier, and more acceptable to the community.